Protein-ligand interactions of druggable protein targets - Souza, Samson Aeloa (Kansas State University, 2020)
A druggable protein target is one in which an exogenous ligand will induce the desired response. In this work, small molecule interactions of three druggable protein targets will be detailed. The first of these is a bacterial enzyme involved in the synthesis of cofactor biotin, which is an essential cofactor exploited across all life domains. It is necessary for fatty acid biosynthesis, gluconeogenesis, and amino acid metabolism. Mammals lack the biosynthetic machinery to produce it and must acquire it in the diet. Meanwhile, bacteria such as E. coli, and M. tuberculosis can synthesize it endogenously. As such, enzymes involved in biotin synthesis are attractive targets in antimicrobial development. Diaminopelargonic acid synthase (BioA) catalyzes the second step in the conserved pathway from starting compounds pimeloyl-CoA and L-alanine. Unlike other bacteria, Bacillus subtilis requires L-lysine as a substrate for transamination of 7-keto-8-aminopelargonic acid (KAPA) to its diamino-product, 7,8-diaminopelargonic acid (DAPA), by BioA. I present kinetic work that suggests a donation of lysine ε-amino group to KAPA. I follow this with the crystal structure of PLP-conjugated lysine as an external aldimine (LLP). The adduct is stabilized by electrostatic interactions between the carboxylate and R410, and pi-cation interactions between the former lys α-amine and two aromatic side chains in the pocket. In the latter segment of this work, I survey ligand interactions of two membrane proteins directly involved in estrogen signaling. The first of these two proteins, G-protein coupled estrogen receptor (GPER), is localized in the endoplasmic reticulum. This research, which was the first to demonstrate in vitro ligand binding with recombinant protein, focuses on steps to produce functional GPER for structural and binding assays. GPER is a potential non-nuclear strategy for breast cancer therapy since 10 – 20 % of diagnoses are estrogen receptor negative. The second estrogen-related protein I will explore is the cytochrome P450 enzyme aromatase (Cyp19). It catalyzes the last biosynthetic step in the production of endogenous estrogens in mammals. To this end, it is a current target in the treatment of hormone-related illnesses and diseases such as endometriosis, ovarian cancer, and breast cancer. Current aromatase inhibitors (AIs), for instance, tamoxifen, are potent, yet they often lead to debilitating side effects. Eventual relapse creates a need for novel breast cancer therapeutics that improve patient outcome. Virtual screening of a library of millions of compounds is often employed to initially uncover drug candidates. I provide activity data of these top hit candidates against a putative Cyp19 allosteric site. Two lead compounds, AR11 and AR13, exhibit potent, anti-aromatase activity comparable to active tamoxifen metabolite, endoxifen. Inhibitory mechanisms of these compounds and the journey to find a promising construct for cocrystallization will be explored. This insight will aid in the search to unearth a novel class of allosteric aromatase inhibitors with diverse toxicity profiles.
Keywords: Estrogen signaling; Aromatase Inhibitor (AI); Breast Cancer target